Fiscal Policy of Economic Development: Comparative Characteristics of Ukraine and Poland - Olha Sliusarchuk; Ruslan Lavrov; Vasyl Kuybida; Maksym Slatvinskyi; Andrii Zelenskyi (Faculty of Economic and Business, 2021)
In order to achieve the purpose outlined, this research uses the following methods: analysis and synthesis; economic and statistical analysis and comparison; economic and mathematical; generalization. The result shows that Poland's fiscal policy aims at developing economic infrastructure and building an economic model of the state based on the manufacture of products with a high share of value-added. However, the fiscal policy of Ukraine does not have significant effects on economic development due to the use of such instruments as public debt and capital expenditures. However, the external debt dependence of the state is relatively high. Nevertheless, it proves that the fiscal policy of Ukraine does not increase the level of economic complexity and development of the processing industry through the implementation of tax benefits. It proposes to increase the efficiency of tax authorities in Ukraine in terms of combating the shadow economy, boost the share of capital expenditures and raise the level of conversion of public debt into economic growth.JEL Classification: E62, F63, H21How to Cite:Sliusarchuk, O., Lavrov, R., Kuybida, V., Slatvinskyi, M., & Zelenskyi, A. (2021). Fiscal Policy of Economic Development: Comparative Characteristics of Ukraine and Poland. Etikonomi, 20(2), xx– xx. https://doi.org/10.15408/etk.v20i2.22013.